2009
DOI: 10.1021/om8007376
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Stable Copper(I) α-Carbonyl Carbenes: Synthesis, Structure, and Mechanistic Studies of Alkene Cyclopropanation Reactions

Abstract: The reaction of [tBu 2 P(NSiMe 3 ) 2 -κ 2 N]Cu(η 2 -C 2 H 4 ) (1) with various aryl diazo esters [p-X-C 6 H 4 ]C(N 2 )[C(O)R] allowed us to synthesize the corresponding R-carbonyl copper(I) carbene complexes 8), where X ) OMe, NO 2 . The rotation barriers around the Cu-C carbene and C carbene -C Ar bonds or their low limits were determined for some of these compounds by 1 H-VT-NMR spectroscopy. Carbene 8g with X ) OMe and R ) OCH(p-Cl-C 6 H 4 ) 2 was isolated in analytically pure, crystalline form as the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 35 publications
2
24
0
2
Order By: Relevance
“…Therefore, copper complex 7 could be described as a copper carbene complex 7' bearing a mesoionic imidazolium-4-olate ring. The Cu1-C1 bond (1.924(6) Å) in 7 is similar to that (1.882(3) Å) for a three-coordinate cationic copper carbene [Cu{=CR 1 (OR 2 )}(MeCN)(OEt 2 )] + (R 1 =( E )-CH=CH-2-furyl; R 2 =menthyl)34, and longer than those (1.822–1.834 Å) observed for the copper carbenes obtained from either diphenyldiazomethane or α-carbonyl diazo compounds30313233. The imidazolium-4-olate ring in 7 is nearly co-planar with the carbene centre, and the neighbouring phenyl ring is tilted with a slightly contracted bond (1.470(8) Å) between the carbene centre and the C ipso (Ph) carbon.…”
Section: Resultssupporting
confidence: 66%
“…Therefore, copper complex 7 could be described as a copper carbene complex 7' bearing a mesoionic imidazolium-4-olate ring. The Cu1-C1 bond (1.924(6) Å) in 7 is similar to that (1.882(3) Å) for a three-coordinate cationic copper carbene [Cu{=CR 1 (OR 2 )}(MeCN)(OEt 2 )] + (R 1 =( E )-CH=CH-2-furyl; R 2 =menthyl)34, and longer than those (1.822–1.834 Å) observed for the copper carbenes obtained from either diphenyldiazomethane or α-carbonyl diazo compounds30313233. The imidazolium-4-olate ring in 7 is nearly co-planar with the carbene centre, and the neighbouring phenyl ring is tilted with a slightly contracted bond (1.470(8) Å) between the carbene centre and the C ipso (Ph) carbon.…”
Section: Resultssupporting
confidence: 66%
“…In the mechanism of the Dötz reaction, he found that chromacyclobutene structures were unrealistic intermediates and instead proposed vinylcarbene complexes as much more stable isomers [64,68,88]. Other research projects of his group included the synthesis of ruthenium–carbene complexes with cis -dichloro ligands for olefin metathesis catalysis [8687 9091 98100 108,132,138,147], the characterization of copper–carbene complexes as intermediates in the cyclopropanation of alkenes [102,106,113,119120], as well as detailed studies into the mechanism of the hydroformylation of alkenes. An improved understanding of this industrially important process was achieved by a combination of ligand design for the rhodium catalysts, kinetic studies, and high-level quantum-chemical calculations [126,135,142,145146 152,155].…”
Section: Peter Hofmann a Multifaceted Organometallic Chemistmentioning
confidence: 99%
“…Copper has also provided some examples for this class of catalytic intermediates. Hofmann first described [44,45,46] the formation in solution of such species upon reacting a Cu(I)-containing iminophosphanamide complex with PhC(N 2 )CO 2 Et (Scheme 6.7a). Later, Warren [47] employed the same strategy starting from a b-diketiminate Cu(I) ethylene complex and diphenyldiazomethane: dinuclear and mononuclear copper-carbene (Scheme 6.7b) complexes were obtained.…”
Section: Fundamentalsmentioning
confidence: 99%